A Hedonic Analysis of Agricultural Land Prices in Pakistan’s Peshawar District - Khan, Salman; Ali, Ghaffar; Shah, Syed Attaullah; Jan, Abbas Ullah; Jan , Dawood; Fayaz, M (Asian Journal of Agriculture and Rural Development, 2016)
This study investigates determinants for agricultural land prices in Peshawar district of Pakistan. A linear hedonic model is used to analyze data set on sale prices of agricultural land parcels and their agricultural, location and environmental characteristics. Results show that agricultural land price is affected positively by soil fertility, amount of irrigation water and closeness to agricultural market. Among location characteristics, distance to city, distance to main road and distance to nearest houses have significant effects on land prices. Agricultural land located closer to city, main road or houses has significantly higher price compared to a more distant land. Environmental degradation such as polluted freshwater bodies has negative effect on nearby agricultural land prices. Based on these findings and review of relevant literature, the study recommends government intervention for conservation of agricultural land, investment in developing agricultural infrastructure such as dams, irrigation canals, roads, transport, agricultural markets, etc., and provision of subsidized fertilizers and other inputs to increase farmers’ returns and change their perception to favour using their land for agriculture.